Peranan Filsafat Pendidikan dalam Pemecahan Problematika Pendidikan Islam - Kholid, Ihyaul; Akhmad Fadli (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Abstract Educational philosophy plays a crucial role in addressing complex and multidimensional educational issues. Educational problems such as moral degradation, identity crises, and irrelevant learning systems require in-depth consideration of the values, goals, and direction of education. Educational philosophy serves as a normative and critical foundation for building a humanistic and transformative education system. This paper aims to explore the contribution of educational philosophy to analyzing and providing solutions to educational problems in Indonesia. The method used is a literature review with a reflective qualitative approach. The results of this study indicate that the application of educational philosophy can strengthen the direction, values, and meaning of Islamic education policies and practices.